UPAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBERDAYAKAN TENAGA PENDIDIK BERSERTIFIKAT PROFESI GURU MENUJU SEKOLAH BERMUTU: (Studi pada SMP Negeri 1 dan 3 Lembang Kabupaten Bandung Barat) - Iin Surtiah; Risna Haryati (LPPM Politeknik Pajajaran ICB, 2022)
The study is titled Principal Leadership in empowering Certified Teachers Grade School Teachers Toward the SMP location in Lembang district. West Bandung. The investigations using descriptive qualitative analytical research methods, data collection techniques with interview, observation and documentation studies. The results of the study as follows: 1 ) Head SMP Lembang has conducted leadership - empowering educators effectively certified teacher professional - grade to the school, with a transformational leadership style and Visioner Leadeship in synergy. 2 ) The effectiveness of the leadership of the Head of SMP Lembang evidenced by mastery of personal competence, managerial, entrepreneurial, social competence and supervision and is able to improve teacher performance by 13.55 % in 2012-2013. 3) Certified Teacher Empowerment Strategies pursued through professional development Sustainable Self Development programs and activities as follows 1) The development of the individual self, 2) Functional Training and Education, 3) In House Training, 4) Collective Activities KKG, MGMPs, PSC, MKSS, 5) Scientific Publications, 6) Innovative activities: workshops, seminars, symposiums. Certified Teacher Empowerment barriers include: 1) Low Motivation to learn some teachers - teachers who are nearing retirement; 2) The low pedagogic competence and professional competence fraction Teacher; 3) Scarcity of School Trustees disciplinary backgrounds Science, Mathematics, and English is required as a resource in the activities of In House Training teachers. 3) The limited time opportunity to pursue continuing education S2/S3 state universities for Culture, Arts and science teachers, English, and Mathematics. For Principal authors recommend including the following: a) the principals must increase continually his quality in transformational and visionery’s leadership to empower effective and professional teachers, b) In House Training for enrichment Instructional Materials Science, Mathematics and English, in addition to the help of School Supervisors should also invoke state university lecturers as a training resource. c) Principals should encourage teachers to continue their education S2/S3 discipline besides linearly Sustainable professional development activities. While those in the appointment of the Head of Department of Education Power School Supervisors should pay more attention to the requirements of academic qualifications and competence of supervisors to prioritize. Teacher: Science, Mathematics, and English to be the supervisor.